A genetic polymorphism that is associated with mitochondrial energy metabolism increases risk of fibromyalgia. Issue 12 (December 2020) - van Tilburg, Miranda A.L.; Parisien, Marc; Boles, Richard G.; Drury, Gillian L.; Smith-Voudouris, Julian; Verma, Vivek; Khoury, Samar; Chabot-Doré, Anne-Julie; Nackley, Andrea G.; Smith, Shad B.; Whitehead, William E.; Zolnoun, Denniz A.; et al.
Abstract : Abstract: Alterations in cellular energy metabolism have been implicated in chronic pain, suggesting a role for mitochondrial DNA. Previous studies reported associations of a limited number of mitochondrial DNA polymorphisms with specific pain conditions. In this study, we examined the full mitochondrial genomes of people with a variety of chronic pain conditions. A discovery cohort consisting of 609 participants either with or without a complex persistent pain conditions (CPPCs) was examined. Mitochondrial DNA was subjected to deep sequencing for identification of rare mutations, common variants, haplogroups, and heteroplasmy associated with 5 CPPCs: episodic migraine, irritable bowel syndrome, fibromyalgia, vulvar vestibulitis, or temporomandibular disorders. The strongest association found was the presence of the C allele at the single nucleotide polymorphism m.2352T>C (rs28358579) that significantly increased the risk for fibromyalgia (odds ratio [OR] = 4.6, P = 4.3 × 10 −4 ). This relationship was even stronger in women (OR = 5.1, P = 2.8 × 10 −4 ), and m.2352T>C was associated with all other CPPCs in a consistent risk-increasing fashion. This finding was replicated in another cohort (OR = 4.3, P = 2.6 × 10 −2 ) of the Orofacial Pain: Prospective Evaluation and Risk Assessment study consisting of 1754 female participants. To gain insight into the cellular consequences of the associated genetic variability, we conducted an assay testing metabolic reprogramming in human cell lines with defined genotypes. The minor allele C was associated with decreased mitochondrial membrane potential under conditions where oxidative phosphorylation is required, indicating a role of oxidative phosphorylation in pathophysiology of chronic pain. Our results suggest that cellular energy metabolism, modulated by m.2352T>C, contributes to fibromyalgia and possibly other chronic pain conditions. Abstract : Supplemental Digital Content is Available in the Text.Full mitochondrial DNA genome sequencing, in combination with assay testing, revealed that cellular energy metabolism, modulated by m.2352T>C, contributes to fibromyalgia and possibly other chronic pain.